PI control application for building air conditioning system - Nasution, Henry (2015)
This manuscript presents a PI controller implementation to control the compressor speed of an air conditioning system based on cooling load to fulfill thermal comfort requirements with higher energy efficiency. Hence, an interface was designed to monitor the experiment, including the controller algorithm. The temperature settings of the conditioned space were 20, 22, and 24oC with internal heat loads of 0 and 1000 W. The experiments conducted indicated that the proposed technique had better temperature control and energy efficiency compared to the thermostat controller.